Energy and Bank Equity Interactions - Shaiban, Mohammed Sharaf; Li, Di; Hasanov, Akram S. (Frontiers in Energy Research, 2021)
Oil price shocks have an adverse effect on real output and bank and industrial profit in most oil-importing countries. We choose a sample of emerging economics to investigate the impact of shocks on equities in these markets. We also include a sample of developed economies for comparison purposes. Utilizing Toda and Yamamoto (1995) causality test to explore the long-run causal relationship between oil prices, we developed banking indices as a proxy of equities and investigate how oil price shocks affect the performance of country-specific banking industries. Besides, an impulse response function and variance decomposition analysis is utilized to respectively examine the dynamic relationship among oil price shocks and macroeconomic factors and the performance of the banking sector. Results vary across different economics in our sample but the magnitude of oil price impact is associated with joint factors namely energy intensity, oil consumption, oil production and oil trade balance. The findings indicate that oil price rises have a negative impact on equity bank indices in developed and emerging economics except for Mexico whose interest rate was not impacted. Generally, these results are consistent with economic theory and evidence provided by previous empirical studies. Our findings suggest that international banks portfolio investors should consider hedging oil price risk.